Metal Halides Based Flexible X‐Ray Detectors. Issue 2 (13th December 2022) - Wang, Shuo; Chen, HuanYu; Jin, Zhiwen
Abstract: Recently, metal halides (MH) flexible X‐ray detectors have attracted remarkable research interest owing to their great potential for non‐planar imaging, which can eliminate imaging ghosting caused by the misfit between the detector and the object. In this review, recent progress in flexible X‐ray detectors, including advanced optimized techniques of MH and novel flexible substrate structures, is summarized. In addition, the main photoelectric property characterizations are depicted along with their detailed physical meaning and analytical methods. To conclude, the existing vital gap between development status and commercial requirements and the corresponding optimization research directions is also covered. Abstract : Metal halides demonstrate high potential in the field of flexible X‐ray detection. This review systematically summarizes these strategies and progresses from material optimization and structure optimization aspects. Furthermore, brief expectations and challenges are listed at the end of this article to outline the possible directions for their further optimization.